ROLE OF POLYMORPHISM OF NF-ΚB1TRANSCRIPTION NUCLEAR FACTOR IN THE PATHOGENESIS OF GENERAL PARODONTITIS - Гасюк, Н.В. (World of Medicine and Biology, 2015)
The article presents the results of molecular genetic study of the role of nuclear transcription factor NF-κB1 in the pathogenesis of generalized periodontitis. Distribution of polymorphic variants of the gene NF-κB1u patients with intact periodontal and genotype (Del/Del) is 5 (11%) with genotype (Del/Ins) 23 (51%) with genotype (Ins/Ins) 17 (38%). Patients with generalized periodontitis is population distribution of genotype (Del/Del) 9 people (16%) with genotype (Del/Ins) under 30 (55%) and (Ins/Ins) 16 (29%). It was found that genotype (Del/Del) is unchanged and the determining factor that causes the development of generalized periodontitis, clinical picture which meets the quickly progressing.